2017
DOI: 10.1186/s12967-017-1298-1
|View full text |Cite
|
Sign up to set email alerts
|

BDNF/TrkB axis activation promotes epithelial–mesenchymal transition in idiopathic pulmonary fibrosis

Abstract: BackgroundNeurotrophins (NT) belongs to a family of growth factors which promotes neurons survival and differentiation. Increasing evidence show that NT and their receptor are expressed in lung tissues suggesting a possible role in lung health and disease. Here we investigated the expression and functional role of the TrkB/BDNF axis in idiopathic pulmonary fibrotic lung (myo)fibroblasts.MethodsLung fibroblast were isolated from IPF patients and characterized for the expression of mesenchymal markers in compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…Among the numerous cytokines that regulate EMT, TGF‐β1 represents a main inducer of EMT in multiple organ systems, since it can independently initiate and complete the entire course of EMT via activating the downstream Smad signalling pathway . Clinical and basic science studies have highlighted the role of TGF‐β1‐triggered EMT in the pathogenesis of lung fibrosis in both IPF patients and animal models treated with bleomycin . In addition, activation of developmental pathways, such as Wnt/LRP/β‐catenin pathway has been implicated in the pathogenesis of pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the numerous cytokines that regulate EMT, TGF‐β1 represents a main inducer of EMT in multiple organ systems, since it can independently initiate and complete the entire course of EMT via activating the downstream Smad signalling pathway . Clinical and basic science studies have highlighted the role of TGF‐β1‐triggered EMT in the pathogenesis of lung fibrosis in both IPF patients and animal models treated with bleomycin . In addition, activation of developmental pathways, such as Wnt/LRP/β‐catenin pathway has been implicated in the pathogenesis of pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Myofibroblast accumulation may occur as a consequence of resident fibroblast to myofibroblast transition, epithelial‐mesenchymal transition (EMT) or by the recruitment of circulating fibroblastic stem cells . Recent studies have highlighted the role of EMT in the pathogenesis of IPF . Epithelial‐mesenchymal transition is controlled by a network of signalling and transcriptional events mediated in part by transforming growth factor (TGF)‐β/Smad signalling pathway .…”
Section: Introductionmentioning
confidence: 99%
“…Transforming growth factor β 1 (TGF- β 1 ) was the most important starting factor of IPF [ 7 ]; it could accelerate the progress with which alveolar epithelial cell is transformed into mesenchymal myofibroblast, and then its specific marker α -smooth muscle actin ( α -SMA) was overexpressed [ 8 ]. During this course of epithelial-mesenchymal transition (EMT), the function of type II alveolar epithelial cell (AECII) such as secreting pulmonary surfactant (PS) would be influenced because of this transformation [ 9 ]. Lamellar body (LB) is an organelle of AECII, which could pack and secrete the pulmonary surfactant [ 10 ]; its ultrastructure could reflect the functional status of AECII.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it was noticed that BDNF/TrkB participated in the activities of fibroblasts. For example, Cherubini and colleagues found that TrkB was expressed in lung fibroblasts, and activation of BDNF/TrkB axis promoted the epithelial–mesenchymal transition in idiopathic pulmonary fibrosis [ 56 ]. Similarly, BDNF/TrkB was associated with pathologic changes of other types of fibroblasts such as airway [ 57 ] and human dermal fibroblast cells [ 58 ].…”
Section: Role Of Bdnf/trkb In Noncardiac Cellsmentioning
confidence: 99%
“…Helan et al reported that PAECs expressed and secreted BDNF in response to hypoxia via an HIF-1-regulated pathway [ 48 ]. Activation of the BDNF/TrkB axis accelerated epithelial–mesenchymal transition in idiopathic pulmonary fibrosis [ 56 ]. In addition, recent studies found that 7,8-DHF enhanced cholinergic contraction of rat gastric smooth muscle via upregulating muscarinic M 3 receptor expression [ 59 ].…”
Section: Role Of Bdnf/trkb In Noncardiac Cellsmentioning
confidence: 99%